Basic Principles of Industrial Electric Power Network Computer Aided Design and Engineering - M. I. Fursanov; I. I. Dul (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A conceptual model for a computer aided design and engineering system has been developed in the paper. The paper presents basic automation process principles including a graphical representation   network and calculation results, convenient user interface, automatic mode calculation, selection of transformer rated power and cross-section area of wires. The developed algorithm and program make it possible to save time and improve quality of project implementation.